Figurative Language in William Shakespeare and William Wordsworth’s Poems - Vivi Melaty Ruslida; Drs. Barnabas Sembiring; Indah Damayanti (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
This research is aimed to investigate the using and the meaning of figurative language in the poems. The sample of this research were ten poems from the two authors separated in 2 century, they are Shakespeare and Wordsworth. This research applied descriptive qualitative method and the objective approach to analyzed the data. The figurative language was analyzed based on Wren and Martin’s theory and also the implied meaning of each figurative language. The figurative language found were presented in the form of table. From the data analysis, it was found all the figurative language in the five poems by Shakespeare except Euphemism and Irony. In Wordsworth’ poems, all the figurative languages were found except Synecdoche and Irony. From the figurative language found and the background of the authors, it was concluded that Shakespeare is a Poetic person, he usually used some beautiful words to describe something. While, Wordsworth is a Romantic person, he usually told about love, emotion and even feeling sadness always related to the lost love. Keywords: Figurative Language, Poems, William Shakespeare, William Wordsworth